MUSICS OF THE WORLD'S CULTURES: A SOURCE BOOK FOR MUSIC EDUCATORS, editors: Barbara Lundquist and C.K. Szego with Bruno Nettl, Ramon Santos and Einar Solbu, published by the Callaway International Resource Centre for Music Education (CIRCME) for the International Society for Music Education (ISME), 1998. 234 pp. - Oehrle, Elizabeth (International Library of African Music, 1999)
pages: 189-190
Keywords: African Music